Оцінка ефективності та впливу путівника на розвиток туризму в Кременчуці - Челомбітько, В. Ф.; Німченко, А. А. (ТОВ «Видавництво Ліра-К», 2025)
This paper evaluates a printed guidebook about Kremenchuk, assessing its effectiveness and impact on local tourism. The guidebook offers key information about the city’s landmarks, history, and culture, benefiting both tourists and residents. The research examines the content, structure, accessibility, and influence of the guidebook, identifying areas for improvement such as updates, digital integration, and interactive features. The study concludes that while the guidebook is valuable for tourism, it needs modernization to better serve contemporary needs.
Keywords: путівник; розвиток туризму